Immunohistochemistry of carcinoembryonic antigen: characterisation of cross-reactions with other glycoproteins. Issue 10 (October 1977) - Isaacson, P; Judd, M A
Abstract : In the course of demonstrating carcinoembryonic antigen (CEA) in normal human small intestine cross-reactivity of specific antiserum against red blood cells, vascular endothelium, and Paneth cell granules was noted. Pretreatment of sections with periodic acid eliminated these cross-reactions without affecting the staining of CEA, indicating that the antigenic determinants shared between CEA and other glycoproteins are in the carbohydrate portion of the molecules. These findings emphasise the caution with which immunohistochemical results should be regarded even when they are apparently well controlled.